936 IMPROVING DELIRIUM SCREENING IN OLDER ADULTS AT THE ROYAL UNITED HOSPITAL, BATH. (14th June 2022) - Cross, R; Trew, C; Howell, K; Dyer, C
Abstract: Introduction: Delirium affects up to 20% of older patients within hospital and is associated with increases in mortality, length of stay, institutionalisation and accelerated cognitive decline in patients with dementia. 30% of cases are preventable. NICE therefore advocates for delirium screening on admission in the elderly and those with cognitive impairment. We aimed to determine the compliance of the RUH Bath with delirium screening. National guidelines advocate for the use of a CAM, 4AT and/or SQiD. The RUH internal policy accepts a full AMT10, AMT4 plus an assessment of alertness, 4AT or a comment from a Consultant geriatrician about the presence of delirium. Method: Notes of 60 patients on geriatric wards were inspected for compliance with screening in the first 24 hours of the patient's admission. Following this, we implemented education sessions for junior doctors, changed the hospital admission proformas and re-wrote the hospital guidelines for delirium to re-emphasise the need for screening. We re-screened the notes 6 months after these changes and then again at 18 months to look for longstanding change. Results: Initially, only 25% of patients were screened according to national standards and 63% met the hospital criteria. At 6 months 52% met the national standard and 82% met the hospital policy. At 18 months 41% the national standard and 87% met the hospital standard. There was also an increase in the proportion of patients being screened for delirium via multiple different method. Conclusion: There has been significant, long-term improvement in delirium screening at the RUH Bath. This is particularly remarkable for the hospital standard where, despite no further intervention, the figures were maintained over 18 months. Despite a slight degradation in those meeting the national standard, the proportion was still higher than pre-intervention.